DIGITAL MEDIA TOOLS AND YOUTH EMPOWERMENT IN ANAMBRA STATE - Anikeze , Nnaemeka Hillary; Okpalaibekwe, U.N (ESUT JOURNAL OF SOCIAL SCIENCES, 2024)
This study empirically investigated Digital Media tools and Youth Empowerment in Anambra State. The study was carried out in Onitsha the capital of Anambra State. The reason for choosing Onitsha is because Onitsha is the largest commercial city in South East with highest population of young entrepreneurs. Specifically the study aims to; ascertain the effect of Youtube on youth skills acquisition and development, examine the effect of facebook on youth accessibility of credit facilities for startup business. The population for the study comprised current metro area population of Onitsha in 2024 which is 1,695,000 residents. However a sample of 400 youths was sampled for the study using Taro Yamane Sampling Techniques. A structured questionnaire designed by the researchers served as the instrument for data collection, data gotten from the respondents were analyzed using simple percentage while chi-square was used for testing of the hypotheses at 0.05 level of significance. The findings of the study revealed that youtube have positive significant effect on youth empowerment in South East Nigeria, facebook has also positive significant effect on youth empowerment in South East Nigeria. Based on the findings, the following recommendations were made; youths should be encouraged to utilize digital tools for self development so as to relevant in today’s world driven by technology, educational centers and skills acquisition training centeres should embrace the use of social media tools in their training curriculum.